Views of Novice Pre-Service Teachers Towards the Use of L1 in the EFL Classroom - Çetin, Kenan; Özbek-Gürbüz, Nurdan (English Studies at NBU, 2022)
This study aimed to explore the views of pre-service teachers (freshman students) at English Language Teaching program at a state university in Turkey towards the use of L1 (mother tongue) in English as a Foreign Language (EFL) classrooms while also investigating their actual use of L1 during an extracurricular teaching event. It also aims to find out if there is a relationship between participants’ educational background in language learning, their views towards use of L1 and their actual use of L1. This study employed a qualitative approach by collecting data through semi-structured interviews and these interviews were supported with field notes taken by the researcher. The findings showed that ELT students mostly favored the use of L2 (target language) in the classroom and stated that it must be used as much as possible; however, some participants also stated that L1 could be used depending on the proficiency of students. The analysis of the interviews showed that there was no relationship between the participants’ actual use of L1 and their educational background for the participants. Finally, the study suggests some implications towards the ELT curriculum in line with the findings.